2023
DOI: 10.1002/1878-0261.13373
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell and spatial analyses reveal the association between gene expression of glutamine synthetase with the immunosuppressive phenotype of APOE+CTSZ+TAM in cancers

Abstract: An immunosuppressive state is regulated by various factors in the tumor microenvironment (TME), including, but not limited to, metabolic plasticity of immunosuppressive cells and cytokines secreted by these cells. We used single‐cell RNA‐sequencing (scRNA‐seq) data and applied single‐cell flux estimation analysis to characterize the link between metabolism and cellular function within the hypoxic TME of colorectal (CRC) and lung cancer. In terms of metabolic heterogeneity, we found myeloid cells potentially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These results suggest that the systems should ideally be run in tandem when autoimmune conditions are considered, at least for murine t-cell data. Additionally, scFEA has been used solely to predict metabolic differences in fatty acid, TCA and glycolysis between non-tumorous osteoblast precursor cells and subsequent differentiated populations associated with kidney disease, as well as a wide range of flux imbalances in tumor associated lymphocytes [49, 50]. In these studies, however, metabolomics validation appeared to be absent.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the systems should ideally be run in tandem when autoimmune conditions are considered, at least for murine t-cell data. Additionally, scFEA has been used solely to predict metabolic differences in fatty acid, TCA and glycolysis between non-tumorous osteoblast precursor cells and subsequent differentiated populations associated with kidney disease, as well as a wide range of flux imbalances in tumor associated lymphocytes [49, 50]. In these studies, however, metabolomics validation appeared to be absent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to glucose and lipid metabolism, TAMs also exhibit elevated consumption of glutamine and arginine. Single-cell analyses revealed that a TAM subpopulation, APOE + CTSZ + TAMs, was characterized by enhanced expression of glutamine synthetase, and the upregulation of glutamine metabolism was positively correlated with the anti-inflammatory and immunosuppressive properties of macrophages [ 65 ]. Accordingly, inhibiting glutamine metabolism showed an antitumour macrophage phenotype shift, including increased expression of TNF, TLR4, CD80 and CD86 but decreased expression of IL-10 [ 66 ].…”
Section: Single-cell Studies Reveal Heterogeneity Of Tamsmentioning
confidence: 99%
“…A subpopulation of TAMs expressing C1QA/B/C is present in multiple cancers, such as colorectal cancer ( 43 ), NSCLC ( 62 ), liver cancer ( 44 ), lung cancer ( 63 ), rental cancer ( 60 , 64 , 65 ), breast cancer ( 8 , 50 ), pancreatic cancer ( 58 ) and cervical cancer ( 57 ). Single-cell and spatial analyses revealed immunosuppressive phenotypes of C1Q + APOE + TAMs in CRCs ( 66 ). The patients with C1QC high TAMs had the best prognosis for cervical cancer, whereas the worst prognosis could appear in patients with C1QC low TAMs ( 57 ).…”
Section: Novel Tam Subpopulations In Different Solid Tumorsmentioning
confidence: 99%